A philosophical retrospective : facts, values, and Jewish identity - Montefiore, Alan (Columbia themes in philosophy., 2010)
As a young lecturer in philosophy and the eldest son of a prominent Jewish family, Alan Montefiore faced two very different understandings of his identity: the more traditional view that an identity such as his carries with it, as a matter of given fact, certain duties and obligations, and an opposing view, emphasized by his studies in philosophy, in which there can be no rationally compelling move from statements of fact-whatever those facts may be-to ""judgments of value."" According to this second view, in the end it is up to individuals to determine their own values and obligations.<B.